Noise Exposure Potentiates Exocytosis From Cochlear Inner Hair Cells - Boero, Luis E.; Payne, Shelby; Gómez-Casati, Maria Eugenia; Rutherford, Mark A.; Goutman, Juan D. (Frontiers in Synaptic Neuroscience, 2021)
Noise-induced hearing loss has gained relevance as one of the most common forms of hearing impairment. The anatomical correlates of hearing loss, principally cell damage and/or death, are relatively well understood histologically. However, much less is known about the physiological aspects of damaged, surviving cells. Here we addressed the functional consequences of noise exposure on the capacity of inner hair cells (IHCs) to release synaptic vesicles at synapses with spiral ganglion neurons (SGNs). Mice of either sex at postnatal day (P) 15-16 were exposed to 1-12 kHz noise at 120 dB SPL, for 1 hour. Exocytosis was measured by tracking changes in membrane capacitance (∆Cm) from IHCs of the apical cochlea. Upon IHC depolarization to different membrane potentials, ∆Cm showed the typical bell-shaped curve that mirrors the voltage dependence of Ca2+ influx, in both exposed and unexposed cells. Surprisingly, from IHCs at 1-day after exposure (d.a.e.), we found potentiation of exocytosis at the peak of the bell-shaped curve. The increase in exocytosis was not accompanied by changes in whole-cell Ca2+ influx, suggesting a modification in coupling between Ca2+ channels and synaptic vesicles. Consistent with this notion, noise exposure also changed the Ca2+-dependence of exocytosis from linear to supralinear. Noise exposure did not cause loss of IHCs, but did result a small reduction in the number of IHC-SGN synapses at 1-d.a.e. which recovered by 14-d.a.e. In contrast, a strong reduction in auditory brainstem response wave-I amplitude (representing synchronous firing of SGNs) and distortion product otoacoustic emissions (reflecting outer hair cell function) indicated a profound hearing loss at 1- and 14-d.a.e. To determine the role of glutamate release in the noise-induced potentiation of exocytosis, we evaluated vesicular glutamate transporter-3 (Vglut3) knock-out (KO) mice. Unlike WT, IHCs from Vglut3 KO mice showed a noise-induced reduction in ∆Cm and Ca2+ influx with no change in the Ca2+-dependence of exocytosis. Together, these results indicate that traumatic noise exposure triggers changes of IHC synaptic function including a Vglut3-dependent potentiation of exocytosis.